Design of Broadband Aperture-Coupled Microstrip Antenna Arrays With Differential Feeding - Ignacio M. Delgado-Lozano; Armando Fernandez-Prieto; Vicente Losada; Rafael R. Boix; Francisco Medina (IEEE Access)
This paper proposes the design of broadband microstrip antennas fed by differential microstrip lines. The designed broadband antennas are composed of two capacitively coupled rectangular stacked patches excited through a dog-bone shaped aperture by short-circuited differential microstrip lines. The short-circuited lines are symmetrically located with respect to the apertures so that their differential-mode (DM) naturally excites the aperture, while their common-mode (CM) is intrinsically rejected. The DM design of the antennas is based on an equivalent second-order filter circuit consisting of two capacitively coupled parallel LC resonators, which helps to ensure the DM broadband impedance matching of the antenna. Two different $2× 2$ arrays using the proposed antennas have been designed, fabricated and measured, one involving four 180° hybrids and three power dividers in the feeding network, the other involving one 180° hybrid and six power dividers. Bandwidths larger than 25%, gains around 12 dBi and cross-polarization below −25 dB have been achieved by the two arrays at a center frequency of 5.5 GHz.